Kearifan Lokal dan Sosial Budaya Suku Maybrat dalam Membuat Koba-Koba (Am) Sebagai Produk Benda Budaya - Maruapey, Azis; Saeni, Fajrianto; Lestaluhu, Rajab; Saeni, Agil; Suaib, Muhammad Ridha (Jurnal Noken: Ilmu-Ilmu Sosial, 2023)
Koba-koba is a unique product of cultural objects (Artifacts) and local wisdom of the Maybrat tribe and has many functions. This research was conducted on the Maybrat tribe community in utilizing forest Pandan as a cultural product in the form of koba-koba (Am). The aim of this research is to find out local wisdom in making koba-koba and the socio-cultural perspective of the Maybrat tribe in interpreting koba-koba. The method in this research is a descriptive method using a Focus Group Discussion (FGD) approach. The results of the research show that the local wisdom of the Maybrat tribe in making and knitting cultural objects in the form of koba-koba is all made from natural materials, starting with the preparation of sheets of Pandan leaves, needles made from bat bones (siwafu) and threads made from gnemon skin fiber (harerem/arus) and stitched by the people. women (mama-mama) form the folds of a coat or umbrella. The socio-cultural perspective of the Maybrat tribe community in making and interpreting koba-koba is a symbol and traditional symbolism that is born from the community and becomes a manifestation of the social and cultural life activities of the Maybrat tribe community in their interaction with their natural environment.